The reliability of linear position transducer, force plate and combined measurement of explosive power-time variables during a loaded jump squat in elite athletes - Hansen, K. T.; Cronin, J. B.; Newton, M. J. (Sports Biomechanics, 2011)
The purpose of this study was to determine the between day reliability of power-time measures calculated with data collected using the linear position transducer or the force plate independently, or a combination of the two technologies. Twenty-five male rugby union players performed three jump squats on two occasions one week apart. Ground reaction forces were measured via a force plate and position data were collected using a linear position transducer. From these data, a number of power-time variables were calculated for each method. The force plate, linear position transducer and a combined method were all found to be a reliable means of measuring peak power (ICC = 0.87-0.95, CV = 3.4%-8.0%). The absolute consistency of power-time measures varied between methods (CV = 8.0%-53.4%). Relative consistency of power-time measures was generally comparable between methods and measures, and for many variables was at an acceptable level (ICC = 0.77-0.94). Although a number of time-dependent power variables can be reliably calculated from data acquired from the three methods investigated, the reliability of a number of these measures is below that which is acceptable for use in research and for practical applications.